Konseling Individu Untuk MeningkatKan Motivasi Belajar Siswa Di SMKS Al-Mahrusiyah Kota Kediri - Sari, Ika Novita; Fitriah, Lailatul; Dori (Fakultas Tarbiyah IAIN Kediri, 2023)
Motivation is a driving force, directing and strengthening a person's behavior in carrying out certain actions. Meanwhile, learning is interpreted as a process characterized by changes in a person's disposition or capabilities. In principle, learning is a student's task, but in fact, not all students have strong motivation and commitment to learning to achieve optimal results. Especially during adolescence, when adapting to physical changes which are also influenced by hormonal, cognitive and emotional changes, students are required to be stable so that they do not experience significant obstacles. This research uses a qualitative approach. The results obtained from individual counseling carried out in four stages starting from identification to evaluation, show that the subject has a below average intellectual capacity so it takes time to capture and manage diverse information. Individuals who do not open up easily, have low self-confidence and a self-concept that has not yet fully formed their own existence can be fundamental things that hinder their motivation to learn. The results of this research are important, as an alternative medium for handling student problems so that you can understand student profiles more deeply.